Being oneself through time: Bases of self-continuity across 55 cultures*. Issue 3 (4th May 2018) - Becker, Maja; Vignoles, Vivian L.; Owe, Ellinor; Easterbrook, Matthew J.; Brown, Rupert; Smith, Peter B.; Abuhamdeh, Sami; Cendales Ayala, Boris; Garðarsdóttir, Ragna B.; Torres, Ana; Camino, Leoncio; Bond, Michael Harris; et al.
Abstract: Self-continuity – the sense that one's past, present, and future are meaningfully connected – is considered a defining feature of personal identity. However, bases of self-continuity may depend on cultural beliefs about personhood. In multilevel analyses of data from 7287 adults from 55 cultural groups in 33 nations, we tested a new tripartite theoretical model of bases of self-continuity. As expected, perceptions of stability, sense of narrative, and associative links to one's past each contributed to predicting the extent to which people derived a sense of self-continuity from different aspects of their identities. Ways of constructing self-continuity were moderated by cultural and individual differences in mutable (vs. immutable) personhood beliefs – the belief that human attributes are malleable. Individuals with lower mutability beliefs based self-continuity more on stability; members of cultures where mutability beliefs were higher based self-continuity more on narrative. Bases of self-continuity were also moderated by cultural variation in contextualized (vs. decontextualized) personhood beliefs, indicating a link to cultural individualism-collectivism. Our results illustrate the cultural flexibility of the motive for self-continuity.